Severity of nasal obstruction can predict the anxiety status of patients with allergic rhinitis but not patients with vasomotor rhinitis. Issue 11 (9th June 2016) - Xi, Lin; Cao, Feifei; Zhang, Yuan; Zhang, Luo
Abstract : Background: Allergic rhinitis (AR) is a chronic systemic allergic disease with an association reported between allergy and anxiety. The objective of the current study was therefore to investigate and retrospectively evaluate the factors that may possibly induce state and trait anxiety among patients with AR and vasomotor rhinitis (VMR). Methods: A total of 253 outpatients suffering from AR and 108 suffering from VMR were assessed for nasal symptoms experienced during the 14 days prior to assessment. All patients scored the severity of their symptoms on a visual analogue scale (VAS) and answered the State‐Trait Anxiety Inventory (STAI) questionnaire to evaluate their state (STAI‐S) and trait (STAI‐T) anxiety scores. Pearson's correlation and multiple regression tests were employed to assess correlations between symptom scores and anxiety status scores. Results: The STAI‐S/T scores were not significantly different between AR and VMR patients; however, for AR patients, STAI‐S and STAI‐T were significantly associated with nasal obstruction and the total nasal symptom scores. Multiple regression analysis further demonstrated that only nasal obstruction significantly influenced both STAI‐S and STAI‐T scores. In contrast, nasal itching and total nasal symptom scores were significantly correlated with the STAI‐S and STAI‐T scores in VMR patients, whereas continuous sneezing VAS scores were significantly associated with only the STAI‐S score. However, multiple regression analysis showed that the associations between any of the 4 nasal symptom scores and STAI‐S and STAI‐T scores were not significant. Conclusion: Nasal obstruction may play a prominent role in mediation of anxiety in patients suffering from AR, but not in patients suffering from VMR.